Acta Universitatis Danubius. Œconomica, Vol. 14, No. 2 - part 4: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
This study related the influence of foreign direct investment inflow on income inequality in South Africa. The paper applied the co-integration regression and used the FDI inflow and income inequality data in South Africa for 2005-2015 to determine. Findings from the Augmented Dickey- Fully (ADF) test showed that increase in FDI inflow has (nonetheless not significant) broadened inequality in South Africa during the period of analysis. In addition, a test for a unit root in uhat arising from the Engle-Granger co-integration relationship test applied the Augmented Dickey-Fuller test. The result indicates that, within the time series examined, there is no long-run relationship between income inequality and foreign direct investment inflow to South Africa. The paper recommends that further research should examine likely effect of governance on income inequality by introducing governance variable into the co-integration regression model to see whether democratic governance in South Africa may have contributed in widening income inequality. Further research might also examine the characteristics of foreign direct investment inflow into the country to see whether it possesses certain attributes such as manufacturing FDI, which could create job for local citizens.